2022
DOI: 10.1002/mma.8323
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative geometric analysis of traveling wave solutions of the modified equal width Burgers equation

Abstract: This paper devotes to the qualitative geometric analysis of the traveling wave solutions of MEW-Burgers wave equation. Firstly, MEW-Burgers equation is transformed into an equivalent planar dynamical system by using traveling wave transformation. Then the global structure of the planar system is presented, and solitary waves, kink waves (anti-kink waves), and periodic waves are found. Secondly, Jacobi stability for the planar system is studied based on KCC theory, and Jacobi stability of any point on the traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The case of ω 1 ε 1 = 0, ω 2 ε 2 = 0 was studied in [17], and the results showed that system (20) presents periodic motion and chaotic behavior. For (n, a, b, r, µ, c, l, ω 1 , ω 2 , ε 1 , ε 2 )=(2, 0.045, 1, 0.08, 0.12, 0.4, 0.2, 1.25, 1.25, 0.5, 0) and the initial value (u, v) = (1, −0.42), system (20) presents periodic motion [17].…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations
“…The case of ω 1 ε 1 = 0, ω 2 ε 2 = 0 was studied in [17], and the results showed that system (20) presents periodic motion and chaotic behavior. For (n, a, b, r, µ, c, l, ω 1 , ω 2 , ε 1 , ε 2 )=(2, 0.045, 1, 0.08, 0.12, 0.4, 0.2, 1.25, 1.25, 0.5, 0) and the initial value (u, v) = (1, −0.42), system (20) presents periodic motion [17].…”
Section: 2mentioning
confidence: 99%
“…This phenomenon means system (20) presents periodic behavior. Let (n, b, r, µ, c, µ, c, l, ω 1 , ω 2 , ε 1 , ε 2 ) = (2, 1, 0.08, 0.12, 0.4, 0.2, 1.25, 2.5, 0.5, 0.5), and the initial values of systems (20) and ( 21) are (u, v) = (1, −0.42) and (u, v, w, z, p, q) = (1, −0.42, 0.8, 0.8, 0.6, 0.6), respectively. When a = 0.039, 0.046, 0.0534, zero is the largest Lyapunov exponent of system (21).…”
Section: 2mentioning
confidence: 99%
See 2 more Smart Citations